KEDUDUKAN BPN RI DALAM MENGHADAPI PROBLEMATIK PUTUSAN NON-EXECUTABLE PENGADILAN TATA USAHA NEGARA TENTANG PEMBATALAN SERTIPIKAT HAK ATAS TANAH (ANOTASI PUTUSAN MAHKAMAH AGUNG RI NO. 158/PK/TUN/2011 TENTANG PEMBATALAN SERTIPIKAT HAK GUNA BANGUNAN NO. 132 - Arvita, Rani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
The existence of a lawsuit in court against the certificate is not a new thing anymore , given stelsel adopted in the system of land registration in Indonesia is negative stelsel positive tendency . If on the certificate that was sued earlier , based on court decisions that have permanent legal force ( inkracht van gewisjde ) should be revoked and canceled by the National Land Agency, but de facto the decision can not be implemented by the National Land Agency with some particular reason , then this is where the role of National Pertanahann Agency to be able to realize the judgment which can not be implemented as Non - Executable decision. In this study will answer perrmasalahan , namely : Why is the National Land Agency wants the Indonesian Supreme Court Decision 158 / PK / TUN / 2011 on Cancellation of Certificate Broking No. 132 on behalf of PT . TOP As the verdict of Non - Executable ?, How the National Land Agency Role In Delivering the Indonesian Supreme Court Decision 158 / PK / TUN / 2011 As a verdict of Non - Executable ? How Legal Certainty The winner of the Indonesian Supreme Court Decision 158 / PK / TUN / 2011 and the Justice and Legal Protection against the owner of Certificate Broking No. 132 Certificate of derivatives and their owners ? To address this problem used approach Legislation , Case Approach , Conceptual Approach , Approach Sociology of Law and Political Law. Based on the survey results revealed that : First , there are two main reasons why the National Land Agency wants the Supreme Court Decision No. 158 / PK / TUN / 2011 as Non - Executable ruling that reasons are normative juridical considerations and Juridical Technical . Pertimbangann normative juridical reason is that the decision of cancellation of the Certificate Broking No. 132 on behalf of PT . TOP is overdue / expired / verjaring , Ultra Petita and filed by the plaintiffs who do not have other interests and there is a decision in the administrative court ruling that the criminal verdict. While consideration juridical reason partly because the decision concerning civil rights and legal justice for the hundreds of people or communities certificate owner derivative or fragment of a Certificate of Right to Building No. 132 certificate as a parent, but it also relates to issues of Local Government Assets and Money State. Second, the role of the National Land Agency in realizing the Supreme Court Decision No. 158 / PK / TUN / 2001 to a decision of Non-Executable is a way to initiate a peace between the parties that the winning parties and the ruling party Certificate holder Broking No. 132 as a party that has been lost. The essence of peace is how the BPN role in creating the conditions that the parties who won the verdict, his rights can still be given, while for the owner of Certificate Broking No. 132 does not need to be canceled. Then after a peace between the parties earlier, the peace agreement must be drawn up in an authentic deed in this case the notarial deed, then a notary deed are then registered to Class I Palembang District Court to get the verdict determination of Non-Executable. Third, the Rule of Law which can be given to the winner of the verdict is that they can still get their rights as they are demanded in the lawsuit, while the owner of Certificate Broking No. 132 does not need to be done for cancellation as a command decision, so that the legal protection and legal justice for the hundreds of citizens derivative of the certificate holder Certificate nno Broking. 132 can still be given. In this study is recommended in order to be reviewed and revised the regulatory legislation has tended to impose to government officials to have to melaksanaka command decision that has ikracht, while there has not yet been set on the criteria that can be used as a benchmark as the ruling Non -Executable as well as an alternative solution, so there will be a legal umbrella for state administration officials were not able to carry out a court decision that has inkracht due to constraints of both factors normative juridical and technical factors. Especially for the internal BPN, it is recommended that in the Minister Substitute Regulation of the National Land Agency No. 3 of 2011 which is currently being created in the Ministry of Agricultural and Spatial / BPN RI put special rules regarding the decision of non-executable and its completion, resulting in the implementation later, this rule can be used as a benchmark by all officials BPN RI in the face of problematic decision of non-executable.